Spitsbergen Through The Times: Intertwined British Mining and Politics in the London Daily Newspaper - Kruse, Frigga (Poljarnyj vestnik, 2022)
British mining and exploration companies were active in Spitsbergen, today Svalbard, between 1904 and 1953. This period was marked by events like the First World War and the signing of the Spitsbergen Treaty, some say Svalbard Treaty, and was therefore politically charged. This article investigates the British Arctic enterprise as portrayed in an influential newspaper, the London Times, where a diverse range of items appeared across the sections Advertising, Business, News, Editorials, and Letters to the Editor. Reports of the London Stock Exchange and the London Gazette serve as factual counterweights to potentially subjective media coverage. In four distinct phases, we see the archipelago’s emergence in global politics, post-war optimism until the settlement of all claim disputes in 1927, a quiet phase caused by global economic depression, and renewed but short-lived optimism after the Second World War. The paper concludes that the British Government took a stance in the Spitsbergen Question already in 1907, and the Times could not be instrumentalised to change this official political opinion. The study offers a baseline for new and comparative research using similar historical sources.